2014
DOI: 10.1371/journal.pone.0090807
|View full text |Cite
|
Sign up to set email alerts
|

Chaihuang-Yishen Granule Inhibits Diabetic Kidney Disease in Rats through Blocking TGF-β/Smad3 Signaling

Abstract: ObjectiveIncreasing evidence shows that TGF-β1 is a key mediator in diabetic nephropathy (DN) and induces renal fibrosis positively by Smad3 but negatively by Smad7. However, treatment of DN by blocking the TGF-β/Smad pathway remains limited. The present study investigated the anti-fibrotic effect of a traditional Chinese medicine, Chaihuang-Yishen granule (CHYS), on DN.Research Design and MethodsProtective role of CHYS in DN was examined in an accelerated type 1 DN induced by streptozotocin in uninephrectomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…In the present study, we found that silymarin downregulated blood glucose level and significantly improved cardiac dysfunction in STZ-induced diabetic rats. When the TGF-b1 receptor is activated, Smad7 dissociates from the TGF-b1 receptor, and Smad2 and Smad3 are activated and phosphorylated (Zhou et al, 2012;Zhao et al, 2014;Xin et al, 2015). In the present study, the level of TGF-b1 was upregulated in DCM, which is consistent with previous studies; however, silymarin administration reduced the level of TGF-b1.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that silymarin downregulated blood glucose level and significantly improved cardiac dysfunction in STZ-induced diabetic rats. When the TGF-b1 receptor is activated, Smad7 dissociates from the TGF-b1 receptor, and Smad2 and Smad3 are activated and phosphorylated (Zhou et al, 2012;Zhao et al, 2014;Xin et al, 2015). In the present study, the level of TGF-b1 was upregulated in DCM, which is consistent with previous studies; however, silymarin administration reduced the level of TGF-b1.…”
Section: Discussionsupporting
confidence: 92%
“…TGF-β1, a key fibrogenic cytokine, mediates glomerulosclerosis and tubulointerstitial fibrosis in DN by enhancing ECM synthesis. The production of key ECM molecules such as collagen and fibronectin was stimulated by TGF-β1/Smad pathway [23]. Therefore, inhibition of TGF-β1 was reported to significantly decrease the high glucose-induced increase in ECM protein expression [39].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 has been found to contribute to the pathogenesis of renal fibrosis by increasing production of collagen and fibronectin in DN [23]. It has also been reported that TGF-β1 increases the expression of some ECM proteins via phosphorylated Smad2/3, leading to fibrosis in renal tissue in diabetic model [11,23].…”
Section: Danshen Injection Suppressed Tgf-β/smad Signaling Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, reversing changes in FN and colIV synthesis might play a key role in delaying the progression of DN. TGF-β is a potent fibrogenic factor (23,24). TGF-β 1 is highly expressed in the kidneys of diabetic animals (25) and humans (26) and contributes to the accumulation of ECM.…”
Section: Discussionmentioning
confidence: 99%